Original paperPatterns of care study of brachytherapy in New South Wales: cervical cancer treatment quality depends on caseload - Thompson, Stephen R.; Delaney, Geoff P.; Gabriel, Gabriel S.; Barton, Michael B. (Journal of Contemporary Brachytherapy, 2014)
Purpose: We previously conducted modelling and a patterns of care study (POCS) that showed gynaecological brachytherapy (BT) was underutilized in New South Wales (NSW), the USA and Western Europe. The aim of the current study was to assess the quality of cervical BT in NSW, and to determine if caseload affects quality of treatment delivery. Material and methods: All nine NSW radiation oncology departments that treated patients with cervical BT in 2003 were visited. Patient, tumour and treatment related data were collected. Quality of BT was assessed using published quality benchmarks. Higher and lower caseload departments were compared. Results: The four higher cervical BT caseload departments treated 11-15 NSW residents in 2003, compared to 1-8 patients for the lower caseload departments. Cervix cancer patients treated at the higher caseload departments were more likely to be treated to a point A dose ≥ 80 Gy (58% vs. 14%, p = 0.001), and to have treatment completed within 8 weeks (66% vs. 35%, p = 0.02). Despite higher point A doses, there was no significant difference in proportions achieving lower than recommended rectal or bladder doses, implying better BT insertions in higher caseload departments. Conclusions: Cervical BT in NSW was dispersed amongst a large number of departments and was frequently of sub-optimal quality. Higher quality BT was achieved in departments treating at least 10 patients per year. It is likely that improved outcomes will be achievable if at least 10 patients are treated per department per year.